Draft genome sequences of Staphylococcus aureus clinical isolate (SA2-IRQ) from a patient with an ear infection - Ibrahim A. Ahmed; Zaid A. Thabit; Yaseen I. Mamoori; Nisreen S. Hasan (Microbiology Resource Announcements, 2026)
ABSTRACT In the current study, we present the genome sequence of Staphylococcus aureus isolated from a patient suffering from an ear infection. The bacterial genome was assembled into 26 contigs, comprising a total of 2,774,206 bp with a GC content of 32.5% and encoded approximately 2,782 genes, including multiple virulence-associated genes.